Revisiting the (Proto-)Feminist Traits of Leonora Christina’s Life and Work through Nina Karin Monsen’s Jammersminne - Peterbauer, Helene (Danske Studier, 2018)
This paper argues that the novel Jammersminne by the Norwegian writer Nina Karin Monsen exhibits striking intertextual references, which are central to a proper understanding of this evidently feminist text, and that the life and work of the Danish noblewoman Leonora Christina forms a central part of Monsen’s intertextual strategy. Beyond the obvious title analogy between Monsen’s epistolary novel Jammersminne and Leonora Christina’s prison recollections Jammers Minde, Monsen’s novel refers to Leonora Christina through a number of subtle hints. A comparative look at Monsen’s Jammersminne and Leonora Christina’s writings will furthermore shed light on the latter’s (alleged) feminist viewpoints, as exhibited in the French autobiography, in Jammers Minde, and in Hæltinners Pryd.